Evaluation of the Effectiveness of Olive (Olea europaea) Leaf and Pomegranate (Punica granatum) Flower Extracts in the Viability of the Protoscolices of Echinococcus granulosus In Vitro - Zainab Ali Hussein (Journal of Global Pharma Technology, 2018)
The present study was conducted for the period from 1/10/2017 up to 1/3/2018 at the Department of Biology - College of Education for Girls-Kufa University. It aims to assess the effectiveness of ethanolic extracts for olive (Olea europaea) leaf and pomegranate (Punica granatum) flower in the viability of protoscolices of Echinococcus granulosus parasite in vitro. The results demonstrated that the ethanolic extracts for olive leaf and pomegranate flower are very effective in the devastation of the protoscolices, and that the mortality rate increases with concentration and duration of exposure to both extracts .The results showed that the ethanolic extracts for olive leaf was more powerful than the ethanolic extracts for pomegranate flower in the mortality of protoscolices, where the LC50 for the mortality of the protoscolices was (9.7) mg/ml and (11.1) mg/ml, respectively, following 15 minutes of exposure to the extracts, while the LC50 for the mortality of the protoscolices (5.9) mg/ml and (6.6) mg/ml respectively, after 60 minutes of exposure to the extracts. The results also showed that the ethanolic extract for olive leaf led to the decimation of the protoscolices in less time than the ethanolic extract for pomegranate flower when exposed to the concentration of (4) mg / ml, where the LT50 of the protoscolices of (44.6) minutes and (79.4) minutes, respectively, while exposed to the concentration of (16) mg/ml, where the LT50 of the protoscolices of (15.7) minutes and (18.3) minutes, respectively. The conclusion from this study that leaves of olive plant and pomegranate flowers as natural materials can be used to kill the protoscolices of the E. granulosus parasite before a surgical procedure to remove the hydatidcysts .Keywords: Olive leaf, Pomegranate flower, Ethanolic extracts, Protoscolices, Echinococcus granulosus, In vitro.